A syringeable immunotherapeutic hydrogel enhances T cell immunity via in-situ activation of STING pathway for advanced breast cancer postoperative therapy - Zhang, Baozhen; Li, Min; Ji, Jiahua; Si, Xinghui; Yin, Xiaojiao; Ji, Guofeng; Ren, Liqun; Yao, Haochen (Frontiers in Immunology, 2025)
Complete surgical resection of advanced breast cancer is highly challenging and often leaves behind microscopic tumor foci, leading to inevitable relapse. Postoperative formation of the immunosuppressive tumor microenvironment (TME) reduces the efficacy of immunotherapies against residual tumors. Although cytotoxic chemotherapeutics exert the capacity to intensify cancer immunotherapy via immunogenic cell death (ICD) effects, systemically administered chemo agents often cannot access residual tumor sites, and fail to elicit antitumor immune responses. Herein, we present a novel syringeable immunotherapeutic hydrogel (SiGel@SN38/aOX40) loaded with the DNA-targeting chemotherapeutic 7-ethyl-10-hydroxycamptothecin (SN38) and the anti-OX40 agonist antibody (aOX40). The sustained in-site release of SN38 and aOX40 activate the stimulator of interferon genes (STING) pathway, intensify type I interferons expression, synergistically facilitate dendritic cell (DC) activation, and initiate persistent T cell mediated immune responses within the surgical resection bed that eliminate residual tumors with no tumor recurrence in 120 days. Collectively, our designed SiGel@SN38/aOX40 induces robust and long-lasting tumoricidal immunity following breast cancer resection and exhibit immense potential for clinical translation.